Local refinement of analysis-suitable T-splines - Scott, M.A.; Li, X.; Sederberg, T.W.; Hughes, T.J.R. (Computer methods in applied mechanics and engineering, 2012)
We develop a local refinement algorithm for analysis-suitable T-splines which does not produce excessive propagation of control points. We then demonstrate its use as an adaptive framework for isogeometric analysis. Analysis-suitable T-splines are a class of T-splines which are linearly independent and form a partition of unity. These properties, coupled with local refinement, make this class of T-splines appealing as a basis for isogeometric analysis.